Geographical analysis of temperature variation in Halabja and its surroundings between 2004-2023 - Amin, Prof. Dr. Hawre Yasin Mohammed; Rashid, Hatav Hamamrad (Sulaimani Journal for Humanities, 2026)
Climatic fluctuation in general and temperature fluctuation in particular is currently considered as one of the current and future changes that directly or indirectly affects humans and natural environment species such as plants and water resources, the entire ecosystem in general The aim of this study is to determine the temperature fluctuations and analyze the annual, seasonal and monthly temperature fluctuations in the study area, which is Halabja and its surroundings between the years (2004-2023), and analyze to show the rate For this purpose, we have divided the research into two main themes: the first (geographical characteristics of the study area), the second (analysis of temperature variation in Halabja and surroundings). The seasonal temperature variation is 11.2% for winter, 5.2% for autumn, 2% for summer, and 7.2% for spring. The monthly variation for July is 2.8% and for December is 31.6% Uncertainty about temperature, direction of changes and their consequences and developing appropriate plans to address their negative impacts on the region.
Keywords: Rarity; deviation; temperature; positive value and negative value; Halabja